"Never a Dull Moment": The Moscow Ambassadorship of Sir Frank Roberts in the Years of the Berlin and Cuban Missile Crises, 1960–1962. Issue 4 (1st October 2016) - Colman, Jonathan
ABSTRACT: This analysis explores the largely unsung Moscow ambassadorship of Britain's Frank Roberts (1960–1962). After examining his Embassy's role in developing cultural and commercial relations, the article addresses Roberts' involvement in the Berlin and Cuban missile crises. In the former case, he made a low-key but important contribution by influencing American policy; in the second, he provided insightful assessments of Soviet attitudes and thinking. Roberts' ambassadorship demonstrated the continued importance of resident embassies and ambassadors, because of the lack of ministerial-level Anglo–Soviet relations and the need to interpret Soviet policy in crisis situations. The research contributes to the literature of diplomatic representation as well as of Anglo–Soviet relations during the Cold War.